In the president's secret service : behind the scenes with agents in the line of fire and the presidents they protect - Kessler, Ronald, 1943- (New York : Crown Publishers, 2009)
Because Secret Service agents are sworn to secrecy, the American public rarely knows what presidents, vice presidents, presidential candidates, and Cabinet officers and their families are really like. If they did, says a former Secret Service agent, "They would scream."
Supervise -- Lancer -- Volunteer -- Threats -- Searchlight -- Daro -- Passkey -- Crown -- Jackal -- Deacon -- Stagecoach -- Rawhide -- Rainbow -- Hogan's alley -- "I forgot to duck" -- The big show -- Timberwolf -- A psychic's vision -- Eagle -- Cutting corners -- POTUS -- Shutting down magnetometers -- Trailblazer -- Living on borrowed time -- Turquoise and Twinkle -- Angler -- Renegade -- Grenade -- Padding statistics -- Dereliction of duty.
Includes index.
Keywords: United States. -- Secret Service -- History; Secret service -- United States -- History; Presidents -- Protection -- United States